Development of an Integrated CMS for the MBKM Student Exchange Program Through the Makassar State University Learning Management System (LMS) Platform - M Syahid Nur Wahid; Hartoto Hartoto; Muhammad Rais; A. Fadil; Muhammad Mahdinul (Jurusan Pendidikan Teknik Elektro, 2025)
The Merdeka Belajar Kampus Merdeka (MBKM) program, specifically the Independent Student Exchange (PMM) program at Universitas Negeri Makassar (UNM), faces challenges regarding inbound student synchronization, course equivalencies, and academic monitoring. This study aims to develop a Content Management System (CMS) integrated with Syam-OK and SIM-MBKM. This study uses the Research and Development (R&D) methodology, emphasizing the system testing process conducted through black box Testing and User Acceptance Testing (UAT). The developed CMS successfully integrated the PMM process end-to-end. The test results showed that the user acceptance rate (UAT) reached 91.5% (Very Good category). Furthermore, the implementation of this system resulted in a 45% increase in PMM administration processing time efficiency and reduced the faculty workload related to student enrollment. This CMS can automatically synchronize inbound student data with the Syam-OK LMS and provide comprehensive academic monitoring features. This integrated CMS application significantly improves PMM academic administration efficiency and learning service quality at the UNM. This system is recommended for the development of more effective MBKM information systems at UNM and other higher education institutions.